2015
DOI: 10.1021/acs.jpcc.5b08726
|View full text |Cite
|
Sign up to set email alerts
|

Failure and Reexamination of the Raman Scattering Enhancement Factor Predicted by the Enhanced Local Electric Field in a Silver Nanorod

Abstract: The Raman scattering of a molecule will be enhanced when it is placed near a metal nanoparticle and the enhancement factor was believed to be proportional to the enhanced local electric field |E|2 at both excitation and scattering wavelengths. The original prediction was derived based on spherical particles but was popularly applied to different configurations. Using electrodynamics theory, we directly calculated the enhancement factor of the Raman scattering at scattering wavelengths when a molecule is placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The most noticeable change is the surface-enhanced Raman scattering which has been extensively studied both experimentally and theoretically. The enhancement factor of the Raman scattering near a spherical nanoparticle has been proposed to be proportional to the enhanced local electric field of the metal nanoparticle at both excitation and scattering wavelengths at the position of the molecule . The theory has been proved to be a success in explaining many experimental measurements. , In 2015, Zhou et al numerically demonstrated that the enhancement factor of the Raman scattering at the scattering wavelength cannot be accurately predicted using the enhanced local electric field when a rod-shaped particle is used . A direct calculation of the scattering cross section of an oscillating dipole with and without the presence of metal nanoparticles should be applied to accurately predict the enhancement factor of the scattering .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most noticeable change is the surface-enhanced Raman scattering which has been extensively studied both experimentally and theoretically. The enhancement factor of the Raman scattering near a spherical nanoparticle has been proposed to be proportional to the enhanced local electric field of the metal nanoparticle at both excitation and scattering wavelengths at the position of the molecule . The theory has been proved to be a success in explaining many experimental measurements. , In 2015, Zhou et al numerically demonstrated that the enhancement factor of the Raman scattering at the scattering wavelength cannot be accurately predicted using the enhanced local electric field when a rod-shaped particle is used . A direct calculation of the scattering cross section of an oscillating dipole with and without the presence of metal nanoparticles should be applied to accurately predict the enhancement factor of the scattering .…”
Section: Introductionmentioning
confidence: 99%
“…The theory has been proved to be a success in explaining many experimental measurements. , In 2015, Zhou et al numerically demonstrated that the enhancement factor of the Raman scattering at the scattering wavelength cannot be accurately predicted using the enhanced local electric field when a rod-shaped particle is used . A direct calculation of the scattering cross section of an oscillating dipole with and without the presence of metal nanoparticles should be applied to accurately predict the enhancement factor of the scattering . Khlebtsov et al studied the enhancement factor of Raman scattering in a rod-shaped particle using both experimental and theoretical approaches and observed discrepancy between the experimental observation and the theoretical prediction calculated using the enhanced local electric field model.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the illuminating source and the field position used to evaluate G 2 PW ( r m , k R ) in the PWA configuration (Figure b) differ dramatically from those used to evaluate G 2 Exp ( R , p loc Exp ) in the experimental configuration (Figure a). Some theoretical works have reported that G 2 PW ( r m , k R ) agrees well with G 2 Exp ( R , p loc Exp ) for the nanosphere monomer, dimer, and array over a wide spectral range based on analytical solutions of Maxwell’s equations using generalized Mie theory. , It was also found that G 2 PW ( r m , k ′) will deviate from G 2 Exp ( R , p loc Exp ) for 1 order of magnitude if the direction of k ′ is perpendicular to R . , Other theoretical work reported that G 2 PW ( r m , k R ) with an incident angle along the direction of − R deviates remarkably in the enhancement factor of the scattering cross section integral over all solid angles of the dipolar emitter–nanorod system over the isolated dipolar emitter system . However, it is still unclear how reliable it is to use G 2 PW ( r m , k R ) to quantitatively predict G 2 Exp ( R , p loc Exp ) (with the radiation angle opposite to the incident angle in PWA) in some important POA systems, such as the nanoparticle–substrate coupled system for SEF and SERS ,, with ultrahigh sensitivity and the scanning probe–substrate coupled system for tip-enhanced Raman spectroscopy (TERS) with ultrahigh spatial resolution (up to subnanometer and even chemical-bond resolution). For example, it has been reported that the calculated enhancement factor of Raman intensities in a TERS system by using PWA can be more than 2 orders of magnitude larger than the measured enhancement factor in the experiments .…”
mentioning
confidence: 77%
“…9,30 It was also found that G 2 PW (r m , k′) will deviate from G 2 Exp (R, p loc Exp ) for 1 order of magnitude if the direction of k′ is perpendicular to R. 9,39 Other theoretical work reported that G 2 PW (r m , k R ) with an incident angle along the direction of −R deviates remarkably in the enhancement factor of the scattering cross section integral over all solid angles of the dipolar emitter−nanorod system over the isolated dipolar emitter system. 40 ) (with the radiation angle opposite to the incident angle in PWA) in some important POA systems, such as the nanoparticle− substrate coupled system for SEF 11 and SERS 24,25,41 with ultrahigh sensitivity and the scanning probe−substrate coupled system for tip-enhanced Raman spectroscopy (TERS) with ultrahigh spatial resolution (up to subnanometer and even chemical-bond resolution). 42−45 For example, it has been reported that the calculated enhancement factor of Raman intensities in a TERS system by using PWA can be more than 2 orders of magnitude larger than the measured enhancement factor in the experiments.…”
mentioning
confidence: 99%
“…Various kinds of silver nanomaterials, such as silver nanoparticles (Ag NPs), silver clusters and silver nanorods have been synthesized. [18][19][20][21][22][23] The optical and electrochemical properties of silver nanomaterials have been extensively explored for trace analysis of a great variety of analyte targets, such as metal ions, proteins, DNA and so on. [24][25][26][27] Dai and coworkers recently reported the detection of Hg 2+ based on Hg 2+ induced aggregation of Ag NPs.…”
Section: Introductionmentioning
confidence: 99%